2021
DOI: 10.48550/arxiv.2103.05853
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multicalibrated Partitions for Importance Weights

Abstract: The ratio between the probability that two distributions R and P give to points x are known as importance weights or propensity scores and play a fundamental role in many different fields, most notably, statistics and machine learning. Among its applications, importance weights are central to domain adaptation, anomaly detection, and estimations of various divergences such as the KL divergence and Renyi divergences between R and P , which in turn have numerous applications. We consider the common setting where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…We show that the upper bound in Equation ( 13) only requires multiaccuracy (as opposed to full multi-group attribution). In contrast, [GRSW21] showed that neither direction of Equation ( 12) is implied by multiaccuracy alone.…”
Section: Sandwiching Bounds From Multi-group Attributionmentioning
confidence: 86%
See 4 more Smart Citations
“…We show that the upper bound in Equation ( 13) only requires multiaccuracy (as opposed to full multi-group attribution). In contrast, [GRSW21] showed that neither direction of Equation ( 12) is implied by multiaccuracy alone.…”
Section: Sandwiching Bounds From Multi-group Attributionmentioning
confidence: 86%
“…The first condition is known as multiaccuracy [GRSW21], and there are many known algorithms that achieve it. It suffices to correctly estimate the marginal term.…”
Section: Multi-group Attributionmentioning
confidence: 99%
See 3 more Smart Citations

Omnipredictors

Gopalan,
Kalai,
Reingold
et al. 2021
Preprint
Self Cite